Alcohol industry sponsorship and hazardous drinking in UK university students who play sport. (1st July 2014) - O'Brien, Kerry S.; Ferris, Jason; Greenlees, Ian; Jowett, Sophia; Rhind, Daniel; Cook, Penny A.; Kypri, Kypros
Abstract Aim To examine whether receipt of alcohol industry sponsorship is associated with problematic drinking in UK university students who play sport. Methods University students (n = 2450) participating in sports were invited to complete a pen‐and‐paper questionnaire by research staff approaching them at sporting facilities and in university settings. Respondents were asked whether they, personally, their team and/or their club were currently in receipt of sponsorship (e.g. money, free or subsidized travel or sporting products) from an alcohol‐related industry (e.g. bars, liquor stores, wholesalers), and whether they had solicited the sponsorship. Drinking was assessed using the Alcohol Use Disorders Identification Test (AUDIT). Results Questionnaires were completed by 2048 of those approached (response rate = 83%). Alcohol industry sponsorship was reported by 36% of the sample. After accounting for confounders (age, gender, disposable income and location) in multivariable models, receipt of alcohol sponsorship by a team (adjusted βadj = 0.41, P = 0.013), club (βadj = 0.73, P = 0.017), team and club (βadj = 0.79, P = 0.002) and combinations of individual and team or club sponsorships (βadj = 1.27, P < 0.002) were each associated with significantly higher AUDIT‐consumption substance scores. Receipt of sponsorship by team and club [adjusted odds ratio (aOR) = 2.04; 95% confidence interval (CI) = 1.04–3.99] and combinations of individual and team or club sponsorships (aOR = 4.12; 95% CI = 1.29–13.15) were each associated with increased odds of being classified a hazardous drinker (AUDIT score >8). Respondents who sought out sponsorship were not at greater risk than respondents, or whose teams or clubs, had been approached by the alcohol industry. Conclusions University students in the United Kingdom who play sport and who personally receive alcohol industry sponsorship or whose club or team receives alcohol industry sponsorship appear to have more problematic drinking behaviour than UK university students who play sport and receive no alcohol industry sponsorship. Policy to reduce or cease such sponsorship should be considered.